Carbonate and Silicate Abundance Indexing in Coarse-Grained River Sediments Using Diffuse Reflection Infrared Spectroscopy (DRIFTS) and Ion-Beam-Induced Luminescence (IBIL) Spectroscopies. Issue 6 (June 2017) - De Lorenzi Pezzolo, Alessandra; Valotto, Gabrio; Quaranta, Alberto
Two different types of spectroscopic methods, namely diffuse reflection infrared spectroscopy (DRIFTS) as a vibrational spectroscopy and ion-beam-induced luminescence (IBIL) as an optical spectroscopy, have been exploited for the analysis of three sand samples collected from the Adige, Bacchiglione, and Brenta rivers (Veneto, Northern Italy) with the aim to set up a procedure for the comparison of the relative abundance of silicates, carbonates, and feldspars. By fitting the spectra, the features corresponding to different geological compounds have been identified and descriptive indexes of their relative amount have been obtained by comparing the peak area ratios.